The menstrual bleeding questionnaire: development and validation of a comprehensive patient‐reported outcome instrument for heavy menstrual bleeding. (23rd January 2015) - Matteson, KA; Scott, DM; Raker, CA; Clark, MA
Abstract : Objective: To develop and validate a patient‐reported outcome measure for women with heavy menstrual bleeding (HMB). Study design: Prospective cohort and cross‐sectional studies. Setting: Outpatient women's health facility. Population: Women aged between 18 and 55 years with and without self‐reported HMB. Methods: Using data from patients and clinicians, we developed a patient‐reported outcome measure for HMB; the Menstrual Bleeding Questionnaire (MBQ). Participants in the validation studies completed demographic and general health questionnaires and either (1) bleeding and quality of life data collected daily on handheld computers and the MBQ after 1 month or (2) the MBQ at enrolment only. A subset of women also completed the Short‐form‐36 (SF‐36) generic quality of life questionnaire. We performed psychometric analyses of the MBQ to assess its internal consistency as well as its content and concurrent validity and ability to discriminate between women with and without HMB. Main outcome measures: Psychometric properties of the questionnaire. Results: Overall, 182 women participated in the MBQ validation studies. We found that the MBQ domains were internally consistent (Cronbach's α  = 0.87–0.94). There was excellent correlation between daily bleeding‐related symptom data and the MBQ completed at 1 month ( ρ  > 0.7 for all domains). We found low to moderate correlation between the MBQ scores and SF‐36 scores ( ρ  = −0.15 to −0.45). The MBQ clearly discriminated between women with and without HMB (mean MBQ score = 10.6 versus 30.8, P  < 0.0001). Conclusions: The MBQ is a valid patient‐reported outcome measure for HMB that has the potential to improve the evaluation of women with self‐reported HMB in research and clinical practice.